Longitudinal analysis reveals high prevalence of Epstein-Barr virus associated with multiple sclerosis - Bjornevik, Kjetil; Cortese, Marianna; Healy, Brian C.; Kuhle, Jens; Mina, Michael J.; Leng, Yumei; Elledge, Stephen J.; Niebuhr, David W.; Scher, Ann I.; Munger, Kassandra L.; Ascherio, Alberto (Science (American Association for the Advancement of Science), 2022)
Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system of unknown etiology. We tested the hypothesis that MS is caused by Epstein-Barr virus (EBV) in a cohort comprising more than 10 million young adults on active duty in the US military, 955 of whom were diagnosed with MS during their period of service. Risk of MS increased 32-fold after infection with EBV but was not increased after infection with other viruses, including the similarly transmitted cytomegalovirus. Serum levels of neurofilament light chain, a biomarker of neuroaxonal degeneration, increased only after EBV seroconversion. These findings cannot be explained by any known risk factor for MS and suggest EBV as the leading cause of MS. Multiple sclerosis is a chronic demyelinating disease of the central nervous system. The underlying cause of this disease is not known, but Epstein-Barr virus is thought to be a possible culprit. However, most people infected with this common virus do not develop multiple sclerosis, and it is not feasible to directly demonstrate causation of this disease in humans. Using data from millions of US military recruits monitored over a 20-year period, Bjornevik et al . determined that Epstein-Barr virus infection greatly increased the risk of subsequent multiple sclerosis and that it preceded the development of disease, supporting its potential role in the pathogenesis of multiple sclerosis (see the Perspective by Robinson and Steinman). —YN Epstein-Barr virus infection precedes symptoms and biomarkers of multiple sclerosis and markedly increases disease risk.